DTMF SIGNALLING CODED SYSTEM AT ROTATING MOVEMENT CONTROLLER OF MONITORING CAMERA - Silvia Handayani, Ade; Latifah Husni, Nyayu (Proceedings of KNASTIK, 2012)
Signalling System of DTMF is coding in the form of tone converted into a binarynumber from the use of the combination of dual tone /frequency produced bypressing the tone of telephone. The use of dual tone is meant for the dialing that isnot interrupted by other frequency, with the frequency limitation that is used in therange of telephone operator. This coded system will be the inputted signal that canmove the motor in contolling the rotating of the camera. In this system, theperformance of DTMF signal sent by transmitted telephone tone is being inputtedto the IC MT8870 as the signal interpreting of DTMF, whereas every DTMFinputted signal has their own frequency range. Then, that signal will become theinput of IC decoder 74LS4514 which will interprete the voltage changing, afterthat, it is inputted to the IC microcontroller AT89C52 in the form of binary. Theoutput of this IC will activate driver that will move the relay of loadsâ€™ controller.From the measurement of DTMF output when being given interruption, thefrequency of pressed tone â€œ2â€ is 1145 Hz, pressed tone â€œ4â€ is 1135 Hz, pressedtone â€œ6â€ is1477 Hz, and pressed tone â€œ8â€ is 1059 Hz.